2018
DOI: 10.1021/acsinfecdis.8b00171
|View full text |Cite
|
Sign up to set email alerts
|

Phagosomal Copper-Promoted Oxidative Attack on Intracellular Mycobacterium tuberculosis

Abstract: Copper (Cu) ions are critical in controlling bacterial infections, and successful pathogens like Mycobacterium tuberculosis (Mtb) possess multiple Cu resistance mechanisms. We report, as proof of concept, that a novel Cu hypersensitivity phenotype can be generated in mycobacteria, including Mtb, through a peptide, DAB-10, that is able to form reactive oxygen species (ROS) following Cu-binding. DAB-10 induces intramycobacterial oxidative stress in a Cu-dependent manner in vitro and during infection. DAB-10 pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 59 publications
(108 reference statements)
2
21
0
Order By: Relevance
“…Alternately, similar findings to those from our study have been reported, including detection of high serum levels of copper during the initial phase of other chronic infectious diseases [31, 33]. Copper ions have been observed to be crucial for the control of intracellular bacteria by optimizing their oxidative attack on Mycobacterium tuberculosis within macrophagic phagolysosomes [34]. Thus, elevated levels could indicate an attempt by the patient’s immune system to control Paracoccidioides spp.…”
Section: Discussionsupporting
confidence: 90%
“…Alternately, similar findings to those from our study have been reported, including detection of high serum levels of copper during the initial phase of other chronic infectious diseases [31, 33]. Copper ions have been observed to be crucial for the control of intracellular bacteria by optimizing their oxidative attack on Mycobacterium tuberculosis within macrophagic phagolysosomes [34]. Thus, elevated levels could indicate an attempt by the patient’s immune system to control Paracoccidioides spp.…”
Section: Discussionsupporting
confidence: 90%
“…The peptide sequence enables efficient permeation into the cytoplasm of M. tuberculosis which resides in the phagosome of infected macrophages. Once accumulated in the phagosome, the conjugate binds abundant Cu 2+ to afford Cu(ATCUN)‐AMP [86] . The Cu(ATCUN) complex generates ROS efficiently, producing more oxidative stress and a bactericidal effect superseding the activity of homologous AMP peptides without the ATCUN motif.…”
Section: Modulation Of Labile Copper Pools By Sequestrationmentioning
confidence: 99%
“…The first insight into the role of copper at the host‐pathogen interface was reported by the finding that copper level fluctuated from 25 to 500 µ m in the phagosome infected with M. tuberculosis [4]. Recently it has been reported that utilizing abundance of copper ions in the M. tuberculosis infected phagosome using peptide that binds copper ions and mediates generation of reactive oxygen species by exploiting the redox property of copper ions [55]. We used mycobacterial strains containing groEL1 ‐WT, groEL1 ‐KO and groEL1 ‐Comp (complemented) gene to study effect of copper on survival at different concentrations.…”
Section: Discussionmentioning
confidence: 99%